Educational Tourismâs Product Strategy at Batur Global Geopark, Kintamani - Bali - Arcana, Komang Trisna Pratiwi; Wiweka, Kadek (International Research Journal of Management, IT & Social Sciences, 2016)
Educational tourism is one of tourism type from the form of alternative tourism that has been developed between the conventional tourism era and modern tourism era. Generally, alternative tourism tends to develop according to sustainability principals. The packaging of tourism destination potential, Batur Global Geopark into educational tourism is a fundamental step of tourism productâs diversification in Bali. Therefore, the tourism potential in Batur-caldera Bali is supporting to be developed or packaged as an educational tourism, which is in accordance with Global Geopark Network (GGN) objectives. This study combines the quantitative and qualitative methodologies (multi-method), which are presented in the form of descriptions. The information will be analysed to determine the strengths, weaknesses, opportunities and threats (SWOT). It formulated appropriate educational tourism product strategies by the elements; attraction, accessibilities, amenities, a supporting organisation (ancillary), activity, available package and community involvement. Furthermore, this study will also identify the factors of strengths, weaknesses, opportunities, and challenges of educational tourism product development in the tourist area of Batur Global Geopark.